A scheduling method for waiting time reduction in node relay-based webcast considering available bandwidth. (1st January 2011) - Gotoh, Yusuke; Yoshihisa, Tomoki; Taniguchi, Hideo; Kanazawa, Masanori
Due to the recent popularisation of digital webcast systems, delivering continuous media data, i.e. audio and video, has been attracted great attention. In node relay-based webcast, the server has better load balance by receiving data concurrently from other several nodes. Conventional methods reduce waiting time by sharing channels and receiving data from them. However, since the number of nodes by which the user can receive the data is one, occupation time of available bandwidth of the node increases. In this paper, we propose a scheduling method to reduce the waiting time for node relay-based webcast. In our proposed method, by considering available bandwidth of each node and producing an effective schedule, the waiting time is reduced.